Uji Performansi Mesin Penggiling Tipe Disc Mill untuk Penepungan Porang - Sutejo, Agus; Putra, Rafa Andika; Ramdani, Gilang; Putri, Annastasha Diandra (abe.fp.unila.ac.id, 2025)
The porang plant is an abundant commodity that has a high chance of becoming an export commodity in the form of fresh tubers, dried chips, and flour. This creates an impetus for processing businesses so a porang tuber flouring machine with good flouring performance is needed. The disc mill type pressing machine is one of the pressing machines that can process porang up to 60- 80 mesh size. This study aimed to analyze and test the performance of the disc mill machine on the results of milling porang. This research was conducted at PT. Daud Teknik Maju Pratama from January to May 2024 using 1 kilogram of porang measuring 1 cm for each treatment. Tests were carried out using three rotational speeds on the disc mill machine (2160 rpm, 2750 rpm, and 3340 rpm). Each treatment was repeated three times. Tests were conducted to obtain data on milling capacity, yield, shrinkage loss, engine power, and milling quality. The performance results showed that the milling capacity of the disc mill machine ranged from 5.96- 9.89 kg/hour. The milling yield value in the 3340 rpm rotational speed treatment was obtained the highest result (91.37%) and the lowest shrinkage (8.63%). The best milling quality results were also obtained in the 3340 rpm rotary speed treatment with the highest value of fine particles 28.54% passing the 80 mesh sieve and the highest percentage reduction in water content of 4.17%. The electric motor power required for disc mill machines with rotating speeds of 2160 rpm, 2750 rpm, and 3340 rpm were 1.0961 kW, 1.3486 kW, and 1.5456 kW, respectively. Keywords: Disc Mill, Flouring, Performance Test, Porang, Porang Flour.